Human Immune Response Varies by the Degree of Relative Cryptococcal Antigen Shedding. (12th December 2015) - Boulware, David R.; von Hohenberg, Maximilian; Rolfes, Melissa A.; Bahr, Nathan C.; Rhein, Joshua; Akampurira, Andrew; Williams, Darlisha A.; Taseera, Kabanda; Schutz, Charlotte; McDonald, Tami; Muzoora, Conrad; Meintjes, Graeme; et al.
Abstract : Capsule shedding in cerebrospinal fluid is associated with inflammatory and Th2-mediated immune responses in HIV-infected individuals with cryptococcal meningitis. These findings provide important insight into the interactions that occur between the host immune system and the infecting strain of Cryptococcus . Abstract: Background.  Cerebrospinal fluid (CSF) cryptococcal glucuronoxylomannan antigen (CrAg) titers generally correlate with quantitative fungal culture burden; however, correlation is not precise. Some patients have higher CrAg titers with lower fungal burdens and vice versa. We hypothesized that the relative discordancy between CrAg titer and quantitative culture burden reflects the relative degree of CrAg shedding by Cryptococcus neoformans and is associated with human immune responses. Methods.  One hundred ninety human immunodeficiency virus-infected individuals with cryptococcal meningitis were enrolled in Uganda and South Africa. We compared initial CSF CrAg titers relative to their CSF quantitative cultures to determine low (n = 58), intermediate (n = 68), or high (n = 64) CrAg shedders. We compared cytokines measured by Luminex multiplex assay on cryopreserved CSF and 10-week mortality across shedding groups using linear and logistic regression and distribution of genotypes by multilocus sequence typing. Results.  The relative degree of CrAg shedding was positively associated with increasing CSF levels of the following: interleukin (IL)-6, IL-7, IL-8, and tumor necrosis factor-α (each P < 0.01), which are all secreted by antigen-presenting cells and negatively associated with vascular endothelial growth factor ( P = .01). In addition, IL-5, IL-13, granulocyte colony-stimulating factor, and macrophage chemotactic protein were decreased in low-CrAg shedders compared with intermediate shedders (each P ≤ .01). Type 1 T-helper cells (Th1) cytokine responses and 10-week mortality did not differ between the shedding groups. Cryptococcal genotypes were equally distributed across shedding groups. Conclusions.  Discordancy between CrAg shedding and expected shedding based on quantitative fungal burden is associated with detectable immunologic differences in CSF, primarily among secreted cytokines and chemokines produced by antigen-presenting cells and Th2.